Blockchain Technology and Quality of Accounting Information: A Systematic Literature Review - Octa Marselita (Jurnal Akuntansi dan Keuangan)
The purpose of this study is to examine the scholarly literature regarding the impact of blockchain technology on the quality of accounting information. ⁠The research methodology is a bibliometrically mapped Systematic Literature Review (SLR) comprising 36 reputable resources. The findings demonstrate numerous advantages of blockchain technology, particularly for accountants. One of the important advantages is distributed recordkeeping, which enhances information transparency and reduces information asymmetry. As a result, it significantly improves the quality of accounting information. ⁠The implication of this research is to provide comprehensive insights into the potential paradigm shift in accounting facilitated by blockchain adoption. Furthermore, the study serves as a foundational platform for future research on the implementation and impact of blockchain in accounting information quality.